Tourism as a means of income generation for developing countries: focus on Nigeria - Ayeni, Dorcas .A. (2008)

(untitled)
Nigeria as a developing country has long depended on oil and agriculture for its foreign exchange earnings. It can positively improve her economy by encouraging and investing in tourism of which she is richly blessed. Tourism in developing countries if focused on will in no small measure contribute to the economic growth. The methodology employed in this paper is direct observation and visits to some tourist sites in Nigeria, combined with relevant literature search. There are tourist attractions which cut across all countries in Africa, but to a large extent they are relatively undeveloped. This paper looks at tourism in some African countries and tourism in Nigeria at a closer observation; attempt is made at highlighting the shortfalls and ways in which these can be developed to help the potentials especially in area of income generation; factors which attract tourists to various potentials are also highlighted. The paper further discusses the benefits of tourism not only to the individual but to a developing Nigerian nation as a means of income generation. The financial benefits, the employment opportunities, developmental possibilities and other attractions that awareness and promotion of these potentials will portend for Nigeria were examined and recommend ways in which resources can be developed to international standard and sustained to generate income.